347 Clinical Outcomes Following Spinal Fusion Using an Intraoperative Computed Tomographic Three-Dimensional Imaging System. (1st August 2016) - Xiao, Roy; Miller, Jacob A.; Sabharwal, Navin C.; Lubelski, Daniel; Alentado, Vincent J.; Healy, Andrew Torre; Mroz, Thomas; Benzel, Edward C.
Abstract: INTRODUCTION: The O-arm Multidimensional Surgical Imaging System provides superior accuracy of pedicle screw insertion compared with free-hand and fluoroscopic approaches. However, no studies have investigated the clinical relevance of increased accuracy. The objective of this study was to investigate the clinical outcomes following spinal fusion using O-arm navigation. We hypothesized that increased accuracy with O-arm navigation decreases the risk of reoperation compared with free-hand and fluoroscopic guidance. METHODS: A consecutive retrospective review of all patients undergoing noncervical spinal fusion at a single tertiary-care institution between December 2012 and December 2014 was conducted. Multivariable linear and Cox proportional hazards regression were used to investigate the association between O-arm navigation and outcomes. RESULTS: Among 1208 procedures, 614 were performed with O-arm navigation, 356 using free-hand techniques, and 238 using fluoroscopy. The most common indication for surgery was spondylolisthesis (56.2%), and most patients underwent posterolateral fusion (75.7%). The average fusion spanned 4.53 vertebral levels. O-arm patients experienced shorter hospital stays than patients undergoing free-hand and fluoroscopy approaches (4.72 vs 5.07 days, P < .01), and multivariable linear regression revealed O-arm as an independent predictor of shorter hospital stays compared with fluoroscopy (β = 0.50, P < .01). O-arm was significantly associated with decreased risk of reoperation for hardware failure (2.9% vs 5.9%, relative risk [RR] 0.50, P = .01), screw misplacement (1.6% vs 4.2%, RR 0.39, P < .01), and all-cause reoperation (5.2% vs 10.9%, RR 0.48, P < .01); these findings were corroborated with Kaplan-Meier survival analysis. Cox proportional hazards modeling revealed that O-arm navigation was an independent predictor of reoperation risk, because free-hand (hazard ratio [HR] 1.97, P < .01) and fluoroscopic (HR 2.32, P < .01) methods both predicted greater risk of reoperation. CONCLUSION: This is the first study to investigate clinical outcomes associated with O-arm navigation following spinal fusion. O-arm navigation predicted decreased length of hospital stay and decreased the risk of reoperation to half the risk of free-hand and fluoroscopic approaches.